2018
DOI: 10.1136/jim-2017-000644
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Flow-Mediated Vasodilation and Critical Coronary Stenosis

Abstract: Endothelial dysfunction, wall thickening and plaque are progressive manifestations of atherosclerosis. Delayed or absent brachial artery dilation after ischemic stimulus has been associated with severity of extracoronary and coronary atherosclerosis. In the current study, we aimed to verify if delayed or absent dilation associates with critical coronary stenosis. We also evaluated the association between coronary stenosis, carotid artery wall thickness and peripheral artery disease. Endothelial function was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Cardiovascular risk factors, including diabetes, alter the endothelial response to SS variations, which can be assessed through flow-mediated (or SS-mediated) vasodilatation of the brachial artery. [12][13][14]17 In the present study, we hypothesized that empagliflozin might influence SS and endothelial function by influencing blood viscosity. Therefore, we accurately measured blood flow velocity, arterial diameter and blood viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular risk factors, including diabetes, alter the endothelial response to SS variations, which can be assessed through flow-mediated (or SS-mediated) vasodilatation of the brachial artery. [12][13][14]17 In the present study, we hypothesized that empagliflozin might influence SS and endothelial function by influencing blood viscosity. Therefore, we accurately measured blood flow velocity, arterial diameter and blood viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…The PWV is associated with major cardiovascular risk factors and a predictor of the prognosis of patients with end-stage renal failure and hypertension. 7) According to Tamaki et al, 4) it is associated with carotid atherosclerosis but not with the severity of cervical carotid artery stenosis. However, it is correlated with the carotid IMT in patients with type 2 DM.…”
Section: Discussionmentioning
confidence: 99%
“…The mean allopurinol and febuxostat doses at treatment target were 384 ± 131 mg and 53 ± 23 mg/day, respectively. The median [interquartile range] time from initiating ULT (visit 2) to achieving sU target (visit 3) was 21 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] weeks for the overall group (for non-tophaceous subjects, 17 [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] weeks; for tophaceous patients, 29 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] weeks).…”
Section: Serum Uratementioning
confidence: 99%
“…Alternatively, we recently reported that, compared to non-gout healthy controls, patients with gout have impairment of both brachial artery flow-mediated dilation (FMD) and nitrate-mediated dilation (NMD), measurements of endothelium-dependent and endothelium-independent (smooth muscle) arterial responsiveness respectively [ 25 ]. Impaired endothelial function assessed by FMD correlates with risk for future coronary events [ 26 29 ], and studies both in vitro and in animal models indicate that urate may impede the ability of endothelial cells to generate nitric oxide and thus limit arterial responsiveness [ 30 , 31 ]. Therefore, both endothelial function and inflammation may be targets for lowering cardiovascular risk in patients with gout.…”
Section: Introductionmentioning
confidence: 99%